Comparison of intrafractional motion with two frameless immobilization systems in surface‐guided intracranial stereotactic radiosurgery. Issue 6 (19th April 2022) - Han, Chunhui; Amini, Arya; Wong, Jeffrey Y.C.; Liang, Jieming; Qing, Kun; Watkins, W. Tyler; Zhang, Sean; Williams, Terence M.; Liu, An
Abstract: Purpose/objectives: The aim of this study is to compare intrafractional motion using two commercial non‐invasive immobilization systems for linac‐based intracranial stereotactic radiosurgery (SRS) under guidance with a surface‐guided radiotherapy (SGRT) system. Materials/methods: Twenty‐one patients who received intracranial SRS were retrospectively selected. Ten patients were immobilized with a vacuum fixation biteplate system, while 11 patients were immobilized with an open‐face mask system. A setup margin of 1 mm was used in treatment planning. Real‐time surface motion data in 37 treatment fractions using the vacuum fixation system and 44 fractions using the open‐face mask were recorded by an SGRT system. Variances of intrafractional motion along three translational directions and three rotational directions were compared between the two immobilization techniques with Levene's tests. Intrafractional motion variation over time during treatments was also evaluated. Results: Using the vacuum fixation system, the average and standard deviations of the shifts were 0.01 ± 0.18 mm, ‐0.06 ± 0.30 mm, and 0.02 ± 0.26 mm in the anterior–posterior (AP), superior–inferior (SI), and left–right (LR) directions, and ‐0.02 ± 0.19°, ‐0.01 ± 0.13°, and 0.01 ± 0.13° for rotations in yaw, roll, and pitch, respectively; using the open‐face mask system, the average and standard deviations of the shifts were ‐0.06 ± 0.20 mm, ‐0.02 ± 0.35 mm, and 0.01 ± 0.40 mm in the AP, SI, and LR directions, and were 0.05 ± 0.23°, 0.02 ± 0.21°, and 0.00 ± 0.16° for rotations in yaw, roll, and pitch, respectively. There was a significant increase in intrafractional motion variance over time during treatments. Conclusion: Patients with the vacuum fixation system had significantly smaller intrafractional motion variation compared to those with the open‐face mask system. Using intrafractional motion techniques such as surface imaging system is recommended to minimize dose deviation due to intrafractional motion. The increase in intrafractional motion over time indicates clinical benefits with shorter treatment time.